Membentuk Generasi Berprestasi Melalui Edukasi Dan Pembinaan Agama Di Desa Pematang Cengkering - Putri, Ayilzi; Rismayani, Rismayani; Mahaputri, Amanda Ulayyah; Hasibuan, Riza Sakhbani; Mawarni, Mawarni; Aprilia, Rima (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Community service activities through the Real Work Lecture (KKN) program aim to make a tangible contribution to society through education and religious guidance, thereby enhancing the knowledge and skills of the community, especially the younger generation, to become individuals who excel both academically and spiritually. This KKN program is in line with one of the main pillars of the Tri Dharma of Higher Education, which is community service. In this program, students are given the opportunity to share knowledge and actively participate in education and the instillation of religion for the generation in Pematang Cengkering Village. The educational and religious activities that have been carried out, such as teaching in elementary schools, mentoring in kindergartens, evening Quran recitation, tutoring, and the Smart Kids Festival, have shown a significant positive impact on the academic development and character of children in Pematang Cengkering Village. These programs not only help students understand their lessons, but also build their self-confidence, strengthen their character, and enhance their spiritual quality, thus shaping a generation that excels in both academic and spiritual aspect.